Selected CC and CXC chemokines in children with atopic asthma - Machura, Edyta; Szczepanska, Maria; Mazur, Bogdan; Chrobak, Ewelina; Ziora, Katarzyna; Ziora, Dariusz; Kasperska-Zajac, Alicja (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : There are only limited data on CC and CXC chemokines regulation in children with asthma. Aim: We compared the serum profile of selected CC and CXC chemokines in patients with atopic asthma and healthy children. Material and methods : Serum concentration of CC chemokines RANTES, MCP-1, and CXC chemokines IP-10, MIG, IL-8, RANTES was measured using cytometric bead array in 44 children with atopic asthma and 17 healthy subjects. Results: The concentration of RANTES was significantly higher and the MIG level was lower in all children with asthma as compared to their control counterparts. We observed increased RANTES and decreased MIG levels also in patients with stable asthma when compared with children in the control group. The IP-10 concentration was similar between the whole asthma group and healthy controls, while significantly increased levels of this chemokine in acute asthma have been observed when compared to stable asthma. For MCP-1 and IL-8, the serum concentration was similar in all compared groups. The MIG concentration correlated positively with IP-10, IL-8, and CRP levels and negatively with the eosinophil count. A negative correlation between the IP-10 and eosinophil count and a negative correlation between FEV1 and IP-10 were found. Conclusions : An increased serum RANTES level in children with asthma may result in enhancement of Th2 lymphocyte recruitment into the airway. A decreased expression of Th1 chemokine MIG in children with stable asthma may contribute to a diminished antagonizing effect on Th2 cytokine production and hence intensify Th2 predominance. An increased IP-10 level in children during an asthma attack suggest that this chemokine is a serological marker of disease exacerbation.